ENVIRONMENTAL IMPACTS OF CLAY MINING IN THE MANGALAPURAM GRAMA PANCHAYAT OF THIRUVANANTHAPURAM DISTRICT, KERALA - A GEOGRAPHICAL APPROACH - Aneesh M R; Suresh S and Mani K (International Journal of Research in Economics and Social Sciences, 2015)
Mining activities undoubtedly contributes to industrial development which in turn boost the national development. On the other hand, the extraction of minerals from the surface of the earth may deteriorate the prevailing environmental conditions and that may take several forms. The present study is an attempt to analyse the geo-environmental dynamics of clay mining in the Mangalapuram gramapanchayat of Thiruvananthapuram District, Kerala. This study incorporates primary as well as the secondary data sources. Vegetation differences are calculated by using NDVI technique with the help of USGS-Landsat Data such as TM and ETM+ for three different periods. NDVI results show that vegetative cover is decreasing drastically and at the same time bare soil area is increasing. Results show that clay mining areas are gradually increasing year by year creating pockmarked landscape with deep trenches and the problems of water contamination and water scarcity.